Implications of an exogenous shock (COVID-19) on wine tourism business: A Portuguese winery perspective. (January 2023) - Guedes, Alexandre; Niklas, Britta; Back, Robin M; Rebelo, João
This study investigates the impact of an exogenous and unexpected shock (COVID-19) on the wine tourism business from the winery's perspective. A sample of 146 Portuguese wineries was surveyed. The econometric results show that the share of wine tourism sales, the amount of dependence on exports and the assertiveness of brand recognition have a structural effect on direct-to-consumer tasting room wine sales, even when the winery's business is disrupted by a shock that degrades the dynamics and flows of international trade. The research establishes a starting point that allows to understand the implications of an exogenous shock on the structure of the winery's business, calling for further research on the firm's economic performance as well as on the consumer's behaviour in a post-pandemic context.